Pengaruh Quarter-Life Crisis Terhadap Personal Growth Initiative pada Dewasa Awal - Linarto, Maria Ivana; Marchella, Sabrina; Putu Erika Valentina; Melati Resda Ceasaria; Andika Galih Raka Dewa; Hioe Ricky Yohanes (Psychopreneur Journal, 2024)
Abstract. Many people experiencing quarter-life crisis at the age of 27th, which considered as emerging adulthood phase, which affect the individual’s personal growth initiative. This research was done to see the impact of the quarter- life crisis towards personal growth initiative. The method used for this research is quantitative correlational with the sample of 18-27 years old and domiciled in Surabaya. Data collection was done with an online questionnaire with total of 107 respondents. Most of them are female, with the percentage of 54.2%, and aged 18 years old, with the percentage of 29.9%. Linear hypothesis test showed significant result with p value <0.001, and ꞵ -0.382. It means that quarter-life crisis has negative impacts toward personal growth initiative, meaning a higher quarter-life crisis would lead to lower personal growth initiative. Through this research, individuals are able to understand that quarter-life crisis can affect their personal growth initiative.